PENDIDIKAN MORAL DALAM FILSAFAT AL-FARABI: INTEGRASI AKAL DAN KEBAJIKAN - Jadmiko Aji Saputro; Fajhri Prima Vandhi; Antony Mahendra; Siti Mahmuda Noorhayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the concept of moral education in Al-Farabi’s philosophical perspective, focusing on the integration of intellect (‘aql) and virtue (faḍīla), and to examine its relevance in contemporary education. This research employs a qualitative approach using a library research method, with primary sources derived from Al-Farabi’s major works, particularly Tahṣīl al-Sa‘āda and Ārā’ Ahl al-Madīna al-Fāḍila, analyzed through a descriptive-analytical framework. The findings indicate that, in Al-Farabi’s thought, intellect serves as the epistemological foundation for understanding goodness, while virtue represents its practical actualization. Their integration constitutes a prerequisite for the formation of a comprehensive moral character and the attainment of ultimate happiness (sa‘āda). These findings align with contemporary moral education paradigms emphasizing the integration of cognitive, affective, and behavioral dimensions. This study concludes that Al-Farabi’s integrative framework of intellect and virtue is relevant as a philosophical foundation for developing holistic moral education. Its implication suggests that moral education should be designed integratively through reflective learning, value habituation, and social experience to foster comprehensive character development.